2018
DOI: 10.4067/s0717-92002018000100071
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of roads and trails on floral diversity and structure of Ganga-Choti forest in Kashmir Himalayas

Abstract: SUMMARYRoads and trails bring deteriorating changes in the structure and composition of forests. The present study investigated the impact of roads and trails on floral diversity and structure of Ganga Choti forest, Kashmir. Phytosociological attributes using systematic quadrate sampling were recorded and analyzed using multivariate ordination techniques including Principal Component Analysis and Cluster Analysis. The total number of species found in the area was 101 belonging to 47 plant families. The dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Hence, in this current study, on comparative analysis, the lesser values have been found for Shannon Index (H), Fisher alpha (FA), Margalef richness index (MRI), in the case of the community structure of forests for Near Nomadic settlements. Similar findings are reported by several previous studies in the Himalayas [43,[60][61][62]. We found a significant difference in all nine plant-related parameters evaluated for the dead plants between forest sites.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, in this current study, on comparative analysis, the lesser values have been found for Shannon Index (H), Fisher alpha (FA), Margalef richness index (MRI), in the case of the community structure of forests for Near Nomadic settlements. Similar findings are reported by several previous studies in the Himalayas [43,[60][61][62]. We found a significant difference in all nine plant-related parameters evaluated for the dead plants between forest sites.…”
Section: Discussionsupporting
confidence: 92%
“…CCA analysis was employed to know the vegetation-environment inter-relationships Iqbal et al 14 ; Khan et al 30 and Ilyas et al 31 . It provides a biplot that directly showed the influences of different environmental factors on the distribution of plant species Mehmood et al 32 ; Khan et al 33 ; Shaheen et al 34 and Zareen et al 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Ecosystems respond to numerous simultaneous changes in the environment as these variations differ the diversity and distribution of communities [ 107 , 108 ]. Vegetation in distributions more closely resembles the changes in soil characteristics [ 109 , 110 , 111 ]. Our results revealed that soil characteristics such as EC, pH, soil texture, OM, K and P had a great impact on plant community distribution and association.…”
Section: Discussionmentioning
confidence: 99%